2014
DOI: 10.1089/apc.2014.0172
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Signs of Renal Damage Despite Normal Renal Function in a Cohort of HIV-Infected Patients: Evaluation of Associated Factors

Abstract: Renal disorders are an emerging problem in HIV-infected patients. We performed a cross-sectional study of the first 1000 HIV-infected patients attended at our HIV unit who agreed to participate. We determined the frequency of renal alterations and its related risk factors. Summary statistics and logistic regression were applied. The study sample comprised 970 patients with complete data. Most were white (94%) and men (76%). Median (IQR) age was 48 (42-53) years. Hypertension was diagnosed in 19%, dyslipidemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Although this study investigated the incidence of CKD, the data on urinalysis were not available. Because persistent proteinuria is one of the diagnostic criteria for CKD and proteinuria can present in patients with normal eGFR value, 32 our findings of CKD incidence (20.6 per 1000 person-years) might be underestimated. Second, although we focused on the investigation of Asian patients, most study subjects were Japanese men, and only a small number of females were included.…”
Section: Discussionmentioning
confidence: 61%
“…Although this study investigated the incidence of CKD, the data on urinalysis were not available. Because persistent proteinuria is one of the diagnostic criteria for CKD and proteinuria can present in patients with normal eGFR value, 32 our findings of CKD incidence (20.6 per 1000 person-years) might be underestimated. Second, although we focused on the investigation of Asian patients, most study subjects were Japanese men, and only a small number of females were included.…”
Section: Discussionmentioning
confidence: 61%
“…5,6 Although pre-marketing studies suggested a favorable safety profile, 7 TDF use has been associated with the development of acute kidney injury, proteinuria, chronic kidney disease (CKD), and the Fanconi syndrome of proximal tubular dysfunction. 812 Kidney biopsy series of patients with TDF-associated kidney injury have demonstrated flattening of proximal tubular epithelial cells and widespread mitochondrial abnormalities. 13,14 Notably, the active drug, tenofovir, is eliminated in urine through active secretion by proximal tubular epithelial cells, 15 with tenofovir influx and efflux mediated by organic anion transporters and multidrug resistance proteins, respectively.…”
mentioning
confidence: 99%
“…13,56,57 Although clinical trials have reported minimal nephrotoxicity, 53,58 observational studies have shown that TDF is associated with higher risks of AKI, proteinuria, nephrogenic diabetes insipidus, and CKD. 14,15,[59][60][61][62][63][64][65][66] Among 10,841 HIV-positive United States veterans, each year of TDF exposure was associated with a 34% higher risk of proteinuria, a 33% higher risk of CKD, and an 11% higher risk of rapid kidney function decline. 14 A subsequent metaanalysis of 17 studies reported faster kidney function decline (23.9 ml/min) and slightly increased risk of AKI (risk difference of 0.7%) among TDF versus non-TDF users.…”
Section: Art Nephrotoxicitymentioning
confidence: 99%